Hydrolysis during hydration of anhydrous calcium sulfosilicate - M.S.Egamberdiyev; I.U.Oripov; Sh.Hakimov; M.G.Akmalov; A.U.Gadoyev; H.B.Asadov (Genius Journals, 2022)
The results of a comprehensive study of the liquid and solid phases of hydrating anhydrous minerals allow us to draw the following conclusion in dilute suspensions, highly basic hydrates are formed in the earliest periods of hydration and over time due to the formation of a dense shell consisting of hydrolysis products primary hydrates that are more stable under these conditions. The presence of CaSO4 in a mixture with β -C2S significantly accelerates the main period of its hydration and promotes better crystallization of neoplasms.
Keywords: sulfa cement; sulfa silicate; hydration; congruent composition